Highly active and stable non noble metal catalyst for oxygen reduction reaction. (13th April 2017) - Zhang, Bodong; Lin, Zhipeng; Huang, Jilin; Cao, Linmin; Wu, Xiaoxian; Yu, Xiang; Zhan, Yunfeng; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Mai, Wenjie; Xie, Weiguang; et al.
Abstract: We report on a highly active and stable FeNC non noble metal catalyst for the oxygen reduction reaction in alkaline solution. To prepare the FeNC non noble metal catalyst graphitic carbon nitride (g-C3 N4 ) and FeCl3 are used as nitrogen and iron source, respectively. Iron is proved essential for the high catalyst activity. The best catalyst shows similar onset potential with commercial Pt/C catalyst in alkaline solution. The paper reveals whether the Fe4 N composite is active in the oxygen reduction reaction. The as prepared catalysts show excellent stability with no change in activity after 10, 000 cycles of acceleration test. The stability is explained by the protection effect of layers of graphitic carbon on the surface. The as prepared catalyst catalyzes the ORR via a four electron process with similar kinetics to that of Pt/C. The high activity and stability make this catalyst good candidate in alkaline fuel cell and metal air batteries. Highlights: FeNC catalyst is studied for the oxygen reduction reaction in alkaline. Iron is proved essential for the high activity. High stability is resulted from the core–shell structure.